State recognition of the right to food at the national level - Margret Vidar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper considers to what extent the human right to food has been recognized by countries in the world, by analysing international obligations and constitutional provisions, bearing in mind that the right to food may be either explicitly or implicitly protected at the constitutional level. It considers constitutional examples from Switzerland, South Africa and India.
Keywords: K33; 330; human rights; right to food; law; constitution; jurisprudence